Development of 3D printed dental resin nanocomposite with graphene nanoplatelets enhanced mechanical properties and induced drug-free antimicrobial activity. Issue 12 (December 2022) - Aati, Sultan; Chauhan, Amandeep; Shrestha, Barsha; Rajan, Sheetal Maria; Aati, Hanan; Fawzy, Amr
Abstract: Objectives: Oral prosthetic rehabilitation has been used for a long time to restore function and natural appearance; however, it is still one of the most challenging areas in dentistry due to its technical fabrication process and biological behavior. Considering the advantages of additive manufacturing technology, this study introduced the feasibility of developing a 3D printed resin-based composition modified with graphene nanoplatelets (GNPs) to improve properties. Methods: Acrylate-based resin was impregnated with different concentrations of GNPs (0.0–0.25 wt%), and then different aspects such as mechanical, physical, biological and antimicrobial were analyzed to evaluate the effectiveness. TEM and SEM were used to characterize GNPs and their existence within the resin. Surface topography and roughness were evaluated using AFM. The degree of conversion and composition were confirmed by FTIR. Mechanical properties were detected using bending strength, microhardness and nanoindentation. Biocompatibility and antimicrobial activities were assessed with oral fibroblast and Candida albicans ( C. albicans ), respectively. In addition, most of the measurements were performed repeatedly after 3 months of storage in artificial saliva to evaluate performance. Results: GNPs improved strength significantly at low concentrations ≤ 0.05 wt%, while the addition up to 0.25 wt% enhanced printed nanocomposite hardness and elasticity. The modification did not induce a toxic response, as its biocompatibility was within the recommended range of biomedical devices. Antimicrobial activity was of prominence, as GNPs showed an outstanding route of reducing C. albicans activity associated with filler proportion. Significance: The embedment of GNPs in 3D printed resin can become a key material for customized applications that require high antimicrobial, stiffness and strength properties. Graphical Abstract: ga1 Highlights: Modified 3D printed material with advanced properties were obtained using GNPs. Polycarboxylate functionalized GNPs showed a durable adhesion after ageing process. GNPs have contributed remarkably to enhance material's flexural modulus, toughness and surface hardness. Developed composite have superior antimicrobial properties associated with GNPs concentration.